Feasibility of Delivering a Tailored Intervention for Advance Care Planning in Primary Care Practice. Issue 9 (4th July 2019) - Paiva, Andrea; Redding, Colleen A.; Iannone, Lynne; Zenoni, Maria; O'Leary, John R.; Fried, Terri R.
Abstract : BACKGROUND/OBJECTIVES: To determine the feasibility of conducting a cluster randomized controlled trial providing individualized feedback reports to increase advance care planning (ACP) engagement in the primary care setting. DESIGN: Pilot cluster randomized controlled trial. SETTING: Two primary care practices selected for geographic colocation. PARTICIPANTS: Adults aged 55 years and older. INTERVENTION: Brief assessment of readiness to engage in (stage of change for) three ACP behaviors (healthcare agent assignment, communication with agent about quality vs quantity of life, and living will completion) generating an individualized feedback report, plus a stage‐matched brochure. MEASURES: Patient recruitment and retention, intervention delivery, baseline characteristics, and stage of change movement. RESULTS: Recruitment rates differed by practice. Several baseline sociodemographic characteristics differed between the 38 intervention and 41 control participants, including employment status, education, and communication with healthcare agent. Feedback was successfully delivered to all intervention participants, and over 90% of participants completed a 2‐month follow‐up. More intervention participants demonstrated progression in readiness than did control participants, without testing for statistical significance. CONCLUSIONS: This pilot demonstrates opportunities and challenges of performing a clustered randomized controlled trial in primary care practices. Differences in the two practice populations highlight the challenges of matching sites. There was a signal for behavior change in the intervention group. J Am Geriatr Soc 67:1917–1921, 2019